PEMANFAATAN LIMBAH KELAPA MENJADI PRODUK RECYCLE RAMAH LINGKUNGAN DI PONDOK PESANTREN DARUL IMAN - Alvita, Livia Rhea; Shintawati, Shintawati; Ermaya, Dewi; Afifah, Dian Ayu; Cendekia, Devy; Elsyana, Vida (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Darul Iman is an Islamic boarding school located in Tanjung Sari Village, Natar District, South Lampung, which is the area around the Rejosari coconut factory. The coconut factory produces waste, one of which is coconut fibre. Coconut fibre can be reused and has a big opportunity to improve the surrounding community's economy, who generally work as farmers and casual daily workers at the factory. This community service activity aims to provide technical knowledge and skills to students in utilising coconut waste into environmentally friendly recycled products to be distributed back to the surrounding community or implemented themselves. The method used in this PkM activity consists of several stages, namely education on processing waste into coco fibre and how to make the product, then continued with technical guidance on making environmentally friendly recyclable products in the form of doormats and brooms. The effectiveness of PKM activities is evaluated by carrying out a pretest and posttest. The evaluation results show that the average posttest percentage score is 90%, getting a score of more than 70, this indicates that there has been an increase in technical knowledge and skills related to making environmentally friendly recyclable products from coconut fibre waste among the Darul Iman Islamic Boarding School students.